Development of 2D Animation Learning Video Media for the TAPPS Learning Model to reduce Mathematics Phobia - Novianti Novianti; Siti Khaulah; T Rafli Abdillah (Jurnal Penelitian Pendidikan IPA, 2023)
2D animated video media emerges as a viable remedy aimed at enhancing student learning outcomes and the effective implementation of the Thinking Aloud Pair Problem Solving (TAPPS) pedagogical approach. The approach adopted involves the utilization of the ADDIE methodology to guide the development of meticulously designed media, a design that has undergone comprehensive validation by multiple assessors, encompassing both content and media scrutiny. This assessment has been conducted across various evaluation criteria. The data collection methodology employed encompassed tests and questionnaires to gauge student reactions. As evidenced by the material validation phase, the average percentage achieved was 77.13%, falling within the "Valid" classification. In tandem, the media validation process yielded an average score of 82.5%, positioning it firmly within the "Highly Valid" classification. Supplementary to the validation assessments, additional scrutiny was directed toward student learning outcomes. The results yielded an average score of 84.35, surpassing the established minimum passing grade of 75. This unequivocally substantiates the comprehensive achievement of learning objectives. Furthermore, student responses towards the learning material were appraised, culminating in an impressive 90.46% satisfaction rate, thus attaining the "Very Good" rating. In light of the meticulous analyses conducted, it is indisputable that the development of 2D animated video media tailored for the TAPPS instructional model stands as a viable and potent strategy to alleviate students' apprehensions towards mathematics